The Differences Level of Resistin between Positive and Negative Helicobacter pylori Gastritis and its Correlation with Nutritional Status - Widya Deli Satuti; Gontar Alamsyah Siregar; Dharma Lindarto; Imelda Rey (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2020)
Background: H. pylori gastritis can be related to people with obesity and metabolic syndrome. The mechanism underlying the relationship between them is suspected to be caused by adipocytokine called resistin. Objective: to analyze the difference level of resistin between positive and negative H. pylori gastritis patients and their relationship with nutritional status.Method: This cross sectional study was done in the Gastroenterology department of General Hospital Adam Malik, Medan, from May to October 2019. Patients with gastritis diagnosed by endoscopy underwent rapid urease test (RUT), resistin, albumin, hemoglobin tests, also body mass index (BMI) and waist circumference (WC) were measured.Results: Sixty gastritis patients found by endoscopic examination, 29 (48.33%) was H. pylori positive and 31 (51.67%) was negative. No significant differences were found between BMI, WC, and albumin against H. pylori gastritis with p values 0.099, 0.055, and 0.528, respectively. Hemoglobin was found significant with a p 0.009. The mean resistin in the positive H. pylori group was 7.62 ng/ml while the negative was 3.23 ng/ml, and statistically significant (p 0.001). There was a strong positive correlation between resistin levels with BMI and WC (BMI p 0.01, r 0.577; WC p 0.001, r 0.592).Conclusion: Resistin levels in gastritis with H. pylori positive are higher than H. pylori negative, body mass index and waist circumference have a strong relationship with resistin levels in patients with positive H. pylori gastritis, hemoglobin is lower in H. pylori positive than negative gastritis.